Respon Pertumbuhan dan Hasil Tanaman Sawi Hijau terhadap Pemberian Pupuk Organik - MAYUN, IDA AYU; ASTININGSIH, A.A. MADE; SUMARNIASIH, MADE SRI (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022), 2022)
One of the efforts to increase soil productivity, fertilization efficiency and yield increase is the application of environmentally friendly fertilization technologies. The purpose of the study was to determine the the growth response and yield of mustard greens to the application of organic fertilizer, and which organic fertilizer gave the highest yield. This research was an experiment in the greenhouse of the Experimental Garden of the Faculty of Agriculture, Udayana University using polybags. The research method used a completely randomized design (CRD), with 3 treatments each with 3 levels, and repeated 4 times so that 36 treatments were obtained. The treatments given were vermicompost fertilizer (KS 0 = no vermicompost, KS 1 = 5 t/ha, KS 2 = 10 t/ha); goat manure (KK 0 = without goat manure, KK 1 = 5 t/ha, KS 2 = 10 t/ha); and organic fertilizers sold on the market (K 0 = without organic fertilizer application, K 1 = 5 t/ha, K 2 = 10 t/ha). Each polybag was filled with 2 plants so that the total plants were 72 plants. Based on the results of the study, it can be concluded that the application of organic fertilizers (compost, vermicompost and goat manure) can increase growth and yield compared to no organic fertilizer application. The application of organic fertilizer 10 tons/ha, gave the highest yield, for a plant height of 35.00 cm; number of leaves 16.25 sheets, 79.29 g, fresh weight and 67.88 g dry weight (compost fertilizer), 34.98 cm, 21.75 sheets, 84.54 g, and 69.72 g (vermicompost fertilizer) , and 35.98 cm, 25.50 sheets, 72.83 g and 61.25 g (goat manure). It is recommended that the cultivation of mustard greens can be done by providing any type of organic fertilizer because it helps growth and yield.